Quality of life as a criterion for assessing the effectiveness of rehabilitation programs in patients with painful external genital endometriosis - E. Begovich; B. Baigalmaa; A. G. Solopova; V. O. Bitsadze; J. Kh. Khizroeva; E. A. Son; Sh. Kh. Zobaid; G. K. Bykovshchenko (Акушерство, гинекология и репродукция, 2023)
Introduction. Chronic pelvic pain negatively affects the quality of life (QoL) of patients with a painful form of external genital endometriosis (EGE) and adversely impacts on the physical, psychoemotional and sexual health of reproductive-age women resulting in distress, maladaptation, anxiety-depressive disorders, disrupted social functioning in family relationships. Aim: to assess the QoL of women with painful EGE after radical treatment in the rehabilitation period by using subjective research methods.  Materials and Methods. We examined 104 female patients of reproductive age (42.4 ± 3.7 years) with painful EGE after radical treatment: group IA – 49 women underwent "active" rehabilitation, group IB – 55 patients underwent "passive" rehabilitation tactics in accordance with standards and National Clinical Guidelines. The assessment of QoL (subjective) was performed using specialized questionnaires: visual analog scale (VAS), PainDETECT questionnaire, Endometriosis Health Profile-30 (EHP-30) questionnaire, Hospital Anxiety and Depression Scale (HADS), Female Sexual Function Index (FSFI). Assessment of QoL parameters was carried out at 6 control time points: before, as well as 5–9 days, 1, 3, 6 and 12 months after surgical treatment.  Results. Patients underwent "active" rehabilitation tactics (group IA) showed prominently reduced pain syndrome, neuropathic component of pain, anxiety-depressive disorders, normalized sexual function and improved all QoL parameters, unlike patients managed with "passive" tactics, who underwent a complex of rehabilitation measures within the framework of National Clinical Guidelines (group IB). More severe EGE course and significantly decreased QoL in patients with painful EGE at "passive" rehabilitation tactics were noted.  Conclusion. Applying a complex personalized rehabilitation program along with multidisciplinary approach in patients with painful EGE after radical treatment can markedly improve overall well-being, timely correct psychoemotional and sexual dysfunction, and therefore prominently increase the patients' QoL.